We Need a Building Code for Building Code - Landwehr, Carl (Communications of the ACM, 2015)
The author looks at computer security, calling for a regulatory code for software development designed to ensure it is written to avoid recognized cybersecurity vulnerabilities. He compares his proposal to the role of building codes for architects and engineers, saying that the large number of cybersecurity personnel being hired today reflect problems in the underlying software and suggesting they are analogous to firefighters putting out many fires caused by poorly designed buildings. Topics include the importance of the software industry playing a lead role in developing such a code and the need to revise it over time to meet evolving cybersecurity challenges.